Water in the Universe - Hanslmeier, Arnold; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2011)
Due to its specific chemical and physical properties, water is essential for life on Earth. And it is assumed that this would be the case for extraterrestrial life as well. Therefore it is important to investigate where water can be found in the Universe. Although there are places that are completely dry, places where the last rainfall happened probably several 100 million years ago, surprisingly this substance is quite omnipresent. In the outer solar system the large satellites of Jupiter and Saturn are covered by a thick layer of ice that could be hiding a liquid ocean below. This of course brings up the question of whether the recently detected extrasolar planets could have some water on their surfaces and how we can detect this. Water molecules are also found in interstellar gas and dust clouds. This book begins with an introductory chapter reviewing the physical and chemical properties of water. Then it illuminates the apparent connection between water and life. This is followed by chapters dealing with our current knowledge of water in the solar system, followed by a discussion concerning the potential presence and possible detection of water on exoplanets. The signature of water in interstellar space and stars are reviewed before the origin of water in the Universe is finally discussed. The book ends with an appendix on detection methods, satellite missions and astrophysical concepts touched upon in the main parts of the book. The search for water in the Universe is related to the search for extraterrestrial life and is of fundamental importance for astrophysics, astrobiology and other related topics. This book therefore addresses students and researchers in these fields.
1 Water on Earth, Properties of Water -- 2 Life and Water -- 3 Water on Planets and Dwarf Planets -- 4 Satellites of Planets in the Solar System -- 5 Water on Small Solar System Bodies -- 6 Water on Extrasolar Planets?- 7 Water in Interstellar Space and Stars -- 8 Water - Where does it Come From? -- 9 Appendix.
Keywords: Physics; Astronomy; Astrobiology; Physics; Astronomy, Astrophysics and Cosmology; Water, general; Astrobiology